2021
DOI: 10.3390/ph14040287
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Lithium Response in Bipolar Disorder

Abstract: Despite being the most widely studied mood stabilizer, researchers have not confirmed a mechanism for lithium’s therapeutic efficacy in Bipolar Disorder (BD). Pharmacogenomic applications may be clinically useful in the future for identifying lithium-responsive patients and facilitating personalized treatment. Six genome-wide association studies (GWAS) reviewed here present evidence of genetic variations related to lithium responsivity and side effect expression. Variants were found on genes regulating the glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Cl - are pumped out through the Na + /K + /Cl - pump transporter, which reduces the intracellular Cl - concentration and causes the hyperpolarization of neurons. Failure to maintain the glutamate-GABA balance may be related to schizophrenia, epilepsy, and anxiety[ 29 ]. Glutamate-GABA regulates the neuronal excitation-inhibition balance, which can cause neurodegenerative diseases and cognitive impairment[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cl - are pumped out through the Na + /K + /Cl - pump transporter, which reduces the intracellular Cl - concentration and causes the hyperpolarization of neurons. Failure to maintain the glutamate-GABA balance may be related to schizophrenia, epilepsy, and anxiety[ 29 ]. Glutamate-GABA regulates the neuronal excitation-inhibition balance, which can cause neurodegenerative diseases and cognitive impairment[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the potential strength of this study is that it highlights that the three established and most widely used approaches to operationalizing the Li response do not produce consistent signals. This is important as nearly all genetic studies of the Li response have reported their findings based on the Alda Cats approach alongside one of the two continuous measures [10]. The disparities in findings across these three traditional response phenotypes are a cause for concern and, whilst imperfect, the revised algorithms do show greater consistency.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal research assessment of the Li response would involve the systematic prospective follow-up of Li-naive cases that are prescribed this medication for the first time [9]. However, this gold-standard approach is complex, so most genetic studies [10][11][12] identify clinical phenotypes of the Li response from ratings of the Retrospective Assessment of Response to Lithium Scale (usually referred to as the Alda scale) [13]. The Alda scale comprises two subscales: The A scale (which measures overall response) and the B scale (which assesses five potential confounders of response).…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for assessing drug response is the prospective clinical trial, but sample sizes for such studies are orders of magnitude smaller (500 vs 50 000) than those currently successful for genome-wide association studies (GWASs). Furthermore, there are few GWASs focusing on lithium response, most suffering from lack of power or failure in replication [ 7 ]. Though more data is being accumulated [ 8 – 14 ], GWAS has so far not had the power to consistently detect reproducible genes.…”
Section: Introductionmentioning
confidence: 99%